LAR, FAR, and PLR as prognostic factors in high-grade urothelial carcinoma of the bladder after surgery - Xie, Huadong; Huang, Yuanbi; Ban, Chengjie; Wei, Wei; Tang, Han; Huang, Qingming; Su, Zhengwei; Cheng, Zhi; Liao, Tianling; Liao, Kangji; Zhou, Liquan; Yi, Xianlin (Frontiers in Oncology, 2025)
ObjectiveWe evaluated the prognostic significance of the Lactate Dehydrogenase-to-Serum Albumin Ratio (LAR), Fibrinogen-to-Albumin Ratio (FAR), and Platelet-to-Lymphocyte Ratio (PLR) in patients with high-grade urothelial carcinoma (HGUC) of the bladder who underwent radical cystectomy (RC). These markers have been reported to be associated with the prognosis of various cancers.MethodsA retrospective analysis was conducted on HGUC patients who underwent RC at Guangxi Medical University Cancer Hospital between January 2013 and June 2021. Optimal cutoff values for LAR, FAR, and PLR were established. Kaplan-Meier survival analysis was used to evaluate survival outcomes, while univariate and multivariable Cox regression analyses identified independent prognostic factors. A nomogram was developed to predict survival, with validation through time-dependent receiver operating characteristic (ROC) curves, calibration plots, and decision curve analysis (DCA).ResultsA total of 180 patients were included, with a follow-up period ranging from 2 to 127 months (49.28 ± 37.87 months). The optimal cutoff values for LAR, PLR, and FAR were 4.46, 139.68, and 0.13, respectively. Multivariable Cox regression identified tumor stage, LAR, PLR, and FAR as independent prognostic factors. Specifically, Stage III (HR = 25.44, 95% CI: 5.20–124.35, p < 0.001) and Stage IV (HR = 11.28, 95% CI: 3.18–40.05, p < 0.001) were independent risk factors for poor survival. A low PLR (HR = 0.45, 95% CI: 0.27–0.76, p = 0.003), low FAR (HR = 0.51, 95% CI: 0.29–0.89, p = 0.018), and low LAR (HR = 0.39, 95% CI: 0.23–0.67, p < 0.001) were independently associated with improved survival. The nomogram demonstrated high accuracy in predicting 1-, 3-, and 5-year overall survival (OS), with area under the curve (AUC) values of 0.866, 0.84, and 0.831, respectively. Further validation confirmed the model’s stability and clinical applicability.ConclusionLAR, PLR, and FAR are promising prognostic factors for HGUC of the bladder following RC, showing substantial potential for prognostic evaluation.